Sustainable Development of Hospitality Enterprises: Concept and Mechanism of Implementation - M. V. Kobyak; A. Makhlouf (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
Today sustainable development affects greatly the rise in economy efficiency in the country and plays an important role for any state in any conditions. The article discusses the concept of sustainable development of hospitality enterprises and mechanism of its implementation by paying special attention to sustainable development of tourism in general. On the basis of criteria of sustainable development of tourism for destinations proposed by the Global Council on Sustainable Tourism the authors in order to estimate the sustainable development of hotels put forward the idea to use classification of hotel enterprise criteria with 5 sections (economic, social, ecological, institutional and information-communicational technologies) connected with aspects of increasing economic benefits for hotel enterprises and local community; to raise corporate social responsibility of hospitality enterprises; to plan their work on condition to minimize the negative consequences for the environment, etc. The author provide practical and methodological recommendations aimed at ensuring sustainable development of these sectors, including monitoring of realization degree and methodology of estimating sustainable development of hospitality enterprises.